Images as Apparitions of the Body: : Ilka Schönbein’s loving game - D'Abronzo, Thais Helena (Revista Brasileira de Estudos da Presença, 2022)
This Article presents aspects of Ilka Schönbein’s trajectory, a German puppeteer and dancer, in particular her game with the puppet and the singular way with which her images and her dance challenge the body. And it is these aspects that makes their images-bodies encounter the transgressive game and movements of Bataille’s and Georges Didi-Huberman’s eroticism. With them and Ilka, image and body are confused and, in this encounter, the image opens to the apparitions of the body: vital and funereal processes that jolt and disrupt the contours of correct human figures. Ilka Schönbein’s images draw our attention to other realities of the body. Her apparitions have a disquieting resemblance to human figures, poised between death, childbirth, and a fusion of bodies.